(untitled) (Research, Society and Development, 2020)
At the level of taxpayer obligations (tax consciousness), there must be an awareness of every taxpayer to calculate, pay, and report assets which are the obligation of every citizen and taxpayer compliance with tax laws and regulations. In addition, every taxpayer has a willingness for someone’s desire and desire to pay taxes that can be interpreted as a value contributed through regulations by not obtaining direct (contra-achievement) services. This research is holistically the duty of the Directorate General of Taxes to carry out guidance and supervision in cutting or collecting taxes, due to inaccuracies that have resulted in administrative sanctions in the form of a 200% fine from the lack of tax deductions or collection The human resources possessed by the tax authorities are actually not ready to implement the self-assessment system and certain interests have emerged to do tax avoidance, tax evasion, and tax mindedness.